TRANSFORMATION OF INDEPENDENT ISLAMIC EDUCATION SYSTEM IN THE MINORITY MUSLIM ENVIRONMENT OF DENPASAR, BALI - Shodiq, Muhammad (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This research aims to analyze the implementation of the Islamic education system in public schools, specifically in public high schools and vocational schools (SMA/SMK Negeri) in Denpasar, Bali. Considering that Hindu communities predominantly inhabit Bali, it is essential to delve deeper into how the Islamic education system operates in educational institutions controlled by the Hindu community, namely SMA/SMK Negeri. The research is field research with a qualitative approach, focusing on Muslim teachers and students as the subjects. The findings of this research indicate that the Islamic education system, initially conducting traditional classroom learning activities, transformed response to the challenging conditions. This transformation involved strengthening the Islamic Education (PAI) curriculum by reinforcing faith, religious values, and religious practices. Furthermore, the transformation expanded various learning activities, spiritual practices, and other religious activities through intra and extracurricular organizations. As a result, the Islamic education system enhanced its image positively regarding extrinsic elements, including the school community and the wider society. This transformation also contributed to notable achievements, exemplified by the school's participation and success in the Halal Olympics organized by the Indonesian Ulama Council (MUI).